Research on the Implementation Effect of Incentive Policies for Prefabricated Buildings Based on System Dynamics: A Chinese Empirical Study - Chunbing Guo; Weidong Yan; Zhenxu Guo (Applied Sciences)
Incentive policies for prefabricated buildings (PBIP) can effectively promote the development of prefabricated buildings (PB) and improve the sustainability of the construction industry, attracting increasing attention from academia and industry. The government has issued many PBIPs (including land policy, plot ratio reward policy, fund policy, financial support policy, preferential tax policy, research and development support policy, and construction process management policy) but the implementation effect of PBIP remains to be clarified, especially regarding the research gap from a dynamic perspective. This study proposes an analytical framework of policy implementation effect based on the chain of “policy text content–policy impact path–policy implementation effect”, aiming to analyze the implementation stage and effect of PBIPs using the system theory analysis method. Combining the main factors affecting the PBIP impact system, a quantitative model containing 50 variables is established based on the system dynamics (SD) model. Finally, using Shenyang, one of China’s first PB pilot cities, as an example, the system simulation and sensitivity analysis of main parameters are carried out in Vensim software. The research results indicate that PBIP in Shenyang has not been fully utilized and targeted improvements and strengthened implementation of PBIP are needed. In the simulation of individual policies, the implementation effect of fund policy is the best, and the impact of research and development support policy on carbon reduction is the most significant. The promotional effect of the policy combination on PB development is more prominent. Using the policy combination reasonably is necessary to leverage the incentive effect fully. Simulation and sensitivity analysis results provide valuable insights for government departments to enhance the implementation effectiveness of the existing PBIP. This study responds to the global trend of promoting sustainable building development. It proposes a new framework for systematically analyzing the implementation effects of PBIPs, filling the research gap in policy evaluation from a dynamic perspective. Its methods and findings are not only applicable to the Chinese context but also provide valuable experience for other countries to develop and optimize PBIPs.